2021
DOI: 10.1007/s00167-020-06421-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning model successfully predicts patients at risk for prolonged postoperative opioid use following elective knee arthroscopy

Abstract: PurposeRecovery following elective knee arthroscopy can be compromised by prolonged postoperative opioid utilization, yet an effective and validated risk calculator for this outcome remains elusive. The purpose of this study is to develop and validate a machine‐learning algorithm that can reliably and effectively predict prolonged opioid consumption in patients following elective knee arthroscopy. MethodsA retrospective review of an institutional outcome database was performed at a tertiary academic medical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…These data may point to a potential transition in factors driving prolonged use between the subacute and chronic periods and warrant further study in larger cohorts. Previously published predictive models for extended postoperative opioid use—all based on retrospective data—show an average AUC of 0.76 for preoperative opioid use 62–73 . Our prospective models show that at 6 weeks post-TKA, preoperative opioid use is a less accurate predictor (AUC=0.64) than prior retrospective models indicate, highlighting the importance of psychosocial and pain-related predictors at this time point.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These data may point to a potential transition in factors driving prolonged use between the subacute and chronic periods and warrant further study in larger cohorts. Previously published predictive models for extended postoperative opioid use—all based on retrospective data—show an average AUC of 0.76 for preoperative opioid use 62–73 . Our prospective models show that at 6 weeks post-TKA, preoperative opioid use is a less accurate predictor (AUC=0.64) than prior retrospective models indicate, highlighting the importance of psychosocial and pain-related predictors at this time point.…”
Section: Discussionmentioning
confidence: 50%
“…Previously published predictive models for extended postoperative opioid use-all based on retrospective data-show an average AUC of 0.76 for preoperative opioid use. [62][63][64][65][66][67][68][69][70][71][72][73] Our prospective models show that at 6 weeks post-TKA, preoperative opioid use is a less accurate predictor (AUC = 0.64) than prior retrospective models indicate, highlighting the importance of psychosocial and pain-related predictors at this time point. In contrast, at 6-month follow-up, preoperative opioid use is an even better prospective predictor than prior work would suggest (AUC = 0.90), and the addition of the above phenotypic characteristics improves it even further.…”
Section: Discussionmentioning
confidence: 58%
“…Although these features provided a solid basis for selecting factors and developing models, some important clinical features were inevitably missing. Several studies with clinical datasets suggested that the missing factors were collected with significant personnel resources or were not routinely collected into clinical datasets [7, 18]. In this study, individual comorbidities, such as hypertension or diabetes, were not documented for each patient as they did not have a medical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include age, tobacco use, and low educational level 33,36 . Given the many high-risk factors, multiple studies have also proposed machine learning models to predict postoperative opioid consumption [37][38][39][40][41][42] . The identification of this high-risk population should become an integral part of any examination provided in a clinical setting.…”
Section: Effect Of Opioids On Orthopaedic Patientsmentioning
confidence: 99%